ASSESSMENT OF THE LENGTH-WEIGHT RELATIONSHIP OF THE ENDEMIC FISH BARBODES CARNATICUS (JERDON, 1849) IN A BIODIVERSITY HOTSPOT, INDIA - RAMYA, VIJAYAKUMAR LEELA; BEHERA, BIJAY KR; DAS, BASANTA KUMAR; KRISHNA, GOPAL; PAVAN KUMAR, ANNAM; PATHAN, MUJHID KHAN (Journal of the Inland Fisheries Society of India, 2026)
The health of an ecosystem is dependent on its flora and fauna; however, endemic species are essential for balancing the ecosystem’s biota. Climate change, environment, gonad maturity, sex, food, and specimen wellness are some of the variables that might affect the fish length-weight association. The current study intends to determine the length-weight relationship (LWR) and condition factor of Barbodes carnaticus, an indigenous species found in the Western Ghats rivers. A total of 153 specimens were collected from four different stocks of the species from Peninsular India during the 2019 monsoon and post-monsoon seasons. The regression coefficient’s value varied between 2.61 and 3.14. The difference between males and females was not significant (independent t-test, p>0.05). The computed pooled length-weight regression equation, Log W = -1.5537+2.7472 Log L, showed negative allometric growth. The fact that the male and female groups’Fulton’s relative condition factor (Kn) values were larger than one suggests that the fish was generally in good health. This is the first report on the length-weight association between several peninsular Indian stocks of B. carnaticus.